Lessons in Innate and Allergic Immunity From Dust Mite Feces and Tick Bites - Keshavarz, Behnam; Erickson, Loren D.; Platts-Mills, Thomas A. E.; Wilson, Jeffrey M. (Frontiers in Allergy, 2021)
Allergic diseases represent a major cause of morbidity in modern industrialized and developing countries. The origins and development of allergic immune responses have proven difficult to unravel and remain an important scientific objective. House dust mites (HDM) and ticks represent two important causes of allergic disease. Investigations into HDM fecal particles and tick bites have revealed insights which have and will continue to shape our understanding of allergic immunity. In the present review, focus is given to the role of innate immunity in shaping the respective responses to HDM and ticks. The HDM fecal particle represents a rich milieu of molecules that can be recognized by pathogen-recognition receptors of the innate immune system. Factors in tick saliva and/or tissue damage resultant from tick feeding are thought to activate innate immune signaling that promotes allergic pathways. Recent evidence indicates that innate sensing involves not only the direct recognition of allergenic agents/organisms, but also indirect sensing of epithelial barrier disruption. Although fecal particles from HDM and bites from ticks represent two distinct causes of sensitization, both involve a complex array of molecules that contribute to an innate response. Identification of specific molecules will inform our understanding of the mechanisms that contribute to allergic immunity, however the key may lie in the combination of molecules delivered to specific sites in the body.